Pengaruh Ukuran Perusahaan, Likuiditas, Leverage Terhadap Cash Efective Tax Rate dengan Risiko Bisnis Sebagai Moderasi pada Perusahaan Terindeks LQ45 di Bursa Efek Indonesia - Ridoan, Ahmad; Rokhmawati, Andewi; Rasuli, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This research aims to test and analyze the influence of Company Size, Liquidity and Leverage with Business Risk as a moderating variable on the Cash Effective Tax Rate (CETR). This type of research is quantitative research. The population in the study were companies indexed LQ45 on the Indonesia Stock Exchange (BEI) from 2020 to 2022. The sample was selected using a purposive sampling method, where of the 45 companies there were 16 companies that met the criteria as samples. The data source used is secondary data obtained from the website www.idx.co.id. Data analysis used multiple linear regression with the help of the SPSS version 26 program. The results of data analysis show that company size as proxied by the Natural Log of Total Assets influences CETR. Liquidity as proxied by the current ratio and leverage as measured by DER influence CETR. Business Risk as proxied by Degree of Operating Leverage (DOL) can moderate the influence of Company Size on CETR, where Business Risk weakens the influence of Company Size on CETR. Business Risk can moderate the influence of Liquidity on CETR, where the influence of Liquidity becomes smaller after being moderated. Leverage moderated by Business Risk has no effect on CETR, so the influence of Leverage on CETR cannot be moderated by Business Risk.